The effect of implicit learning on functional connectivity in schizophrenia - Asli Ceren Hinc; Asli Ceren Hinc; Simay Selek; Ibrahim Sungur; Ibrahim Sungur; Kaan Keskin; Kaan Keskin; Furkan Yazici; Furkan Yazici; Mehmet Can Erata; Mehmet Can Erata; Yigit Erdogan; et al. (Frontiers in Psychiatry)
IntroductionNeuronal plasticity, or the ability to change and adapt in response to experiences, learning, or environment, is frequently disrupted in schizophrenia and contributes to disease-associated cognitive deficits and functional impairments.MethodsIn this study, we investigated the neuroplasticity alterations of schizophrenia patients in the cortico-striato-cerebellar circuits associated with implicit learning using a reward-enhanced Serial Reaction Time Task (SRTT) by resting-state functional MRI (rs-fMRI). Forty-two schizophrenia patients and 25 healthy controls underwent pre- and post-task rs-fMRI to evaluate changes in functional connectivity.ResultsBehavioral results indicated that all participants demonstrated shorter reaction times during sequential blocks, schizophrenia patients exhibited lower accuracy suggesting diminished implicit learning. Schizophrenia patients exhibited increased connectivity across cortico-striatocerebellar circuits, which became even more robust and widespread following task completion. Despite impaired performance, this post-task hyperconnectivity may reflect a compensatory mechanism attempting to recruit additional neural resources—albeit in a dysfunctional or inefficient manner. Data-driven analyses confirmed the post-task differences between groups, identifying task-induced connectivity changes in thalamo-cortico-cerebellar circuits as the strongest predictors of a group membership.DiscussionThese findings underscore the role of neuroplasticity impairments in schizophrenia-related cognitive deficits, highlighting potential neural markers for clinical differentiation and paving the way for targeted interventions.